Can Facebook Informational Use Foster Adolescent Civic Engagement?. Issue 3 (17th April 2015) - Lenzi, Michela; Vieno, Alessio; Altoè, Gianmarco; Scacchi, Luca; Perkins, Douglas D.; Zukauskiene, Rita; Santinello, Massimo
Abstract: The findings on the association between Social Networking Sites and civic engagement are mixed. The present study aims to evaluate a theoretical model linking the informational use of Internet‐based social media (specifically, Facebook) with civic competencies and intentions for future civic engagement, taking into account the mediating role of civic discussions with family and friends and sharing the news online. Participants were 114 Italian high school students aged 14–17 years (57 % boys). Path analysis was used to evaluate the proposed theoretical model. Results showed that Facebook informational use was associated with higher levels of adolescent perceived competence for civic action, both directly and through the mediation of civic discussion with parents and friends (offline). Higher levels of civic competencies, then, were associated with a stronger intention to participate in the civic domain in the future. Our findings suggest that Facebook may provide adolescents with additional tools through which they can learn civic activities or develop the skills necessary to participate in the future.